BlockGen a concrete hollow block building model generator program for nonlinear analysis using rigid body spring-discrete element method - Ragudo, Carl Chester Q.; Tingatinga, Eric Augustus J.; Malabanan, Arwin (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Concrete hollow block (CHB) structures are one of the most prevalent type of residential buildings and understanding their performance during earthquakes uses computer models that reduce the cost and increase the speed of future studies. However, the development of these models require significant effort in modifying the numerical parameters and validating them with experimental data. This study developed an automatic input file generator program, BlockGen, for Rigid Body Spring-Discrete Element Method (RBS-DEM) models of CHB houses. RBS-DEM uses rigid bodies connected by spring systems in which the displacements of the structure can be fully described by the motion of the rigid bodies, while the strain energy is stored in the springs. BlockGen is a cross-platform console application written in C language that generates rigid bodies with positions, dimensions, and orientations consistent with building attributes, wall geometry (i.e. presence of windows and doorways), and common construction practices. Interfaces, which are surfaces between blocks, are defined for the purpose of assigning the connectivity and determining the parameters of springs. Pertinent information is read from a text file using a proposed format and outputs a text file containing relevant information on the rigid bodies and springs. The program was used to generate models of typical CHB houses of varying geometry and properties, and houses from available shaking table experiments. This study also compiled response spectra and displacement-time histories from shaking table experiments for future use.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Structural analysis (Engineering) -- Computer programs; Hollow bricks